Transformasi Internasionalisasi Perguruan Tinggi Menuju World Class University - Umi Zulfa (LITERASI (Jurnal Ilmu Pendidikan), 2012)
World Class University (WCU) is phenomenon that recently becomes the aims of higher education in the world, including in  Indonesia. For going to WCU, higher education can do the transformation throughout education internationatlization program.  Internationaliztion of higher education itself is the integration process of international and intercultural dimention into the function of teaching, research and service from whole institution. Trought approach and several internationalization strategy, so higher education can do transformation goes to WCU. Catching from these necessities, Indonesian government released policy about internationalization of higher education program.Key words: World Class University, transformation, internationalization